Identification of Massive Deaths of Drowning Cases due to Ship Accident - Fedakar, Recep; Eren, Bülent; Türkmen, Nursel; Akan, Okan (The Bulletin of Legal Medicine, 2003)
We aimed to investigate physical examination, autopsy findings and identification studies of African victims drown after ship accident in Aegean Sea February 2004. We examined the reports of 25 cases autopsied in Bursa Morgue Department of the Turkish Council of Forensic Medicine, retrospectively. On the external examination of 9 female and 16 male cases, we found findings towards identification like tattoo, teeth crowning, finger anomalies in some cases and female circumcision in 3 females. The photographs of all cases were taken and samples were taken for DNA analysis. The cause of death of all cases were reported as due to drowning. Only 3 cases were identified. We discussed the findings of the cases and the procedures towards victim identification. It was exposed that the necessity of international collaboration for foreign citizen victim identification. Key words: Ship accident, massive deaths, identification, external examination, autopsy.